Analysis and simulation of active clamped quasi-resonant DC link inverter - Aksoy, I; Bodur, H; Obdan, H; Bekiroglu, N (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2005)
This paper proposes a simulation developed to use pulse width modulation (PWM) technique with the active clamped quasi-parallel resonant dc link (ACQPRDCL) inverter in order top increase the advantages of the PWM which allows to reduce the switching losses of the power devices. The new ACQPRDCL ensures zero crossing for a time period, and at any time required for soft swiching(SS) and PWM operation of the inverters, respectively. The principle of operation is analyzed and verified by PSPICE simulations.
Keywords: PWM; ACQPRDCL; ACQPRDCL inverter; soft switching; soft switching inverter; simulation; SOFT-SWITCHED PWM; MOTOR-DRIVES; VOLTAGE; CONVERTERS; TOPOLOGY; Engineering